ANALYSIS OF FACTORS CAUSING PENDING BPJS CLAIMS IN EMERGENCY CASES AT PANDAN ARANG REGIONAL GENERAL HOSPITAL BOYOLALI - Utami, Yeni Tri; Rahayuningsih, Lilik Anggar Sri; Itasari, Pipit; Bobo, Cesilia Juliana da Cruz Tasi; Silva, Densiana Nunes da (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Pending BPJS claims for emergency cases is one of the obstacles in the healthcare payment process, impacting the smooth operation of the hospital. At Pandan Arang Regional Hospital (RSUD) in Boyolali, the number of pending claims is quite high, with 1,045 pending claims in 2024. This study aims to analyze the factors causing pending BPJS claims for emergency cases at Pandan Arang Regional Hospital in Boyolali. The research method used is descriptive with a retrospective approach. The study population of pending BPJS emergency claims was 1,045, with a sample of 289 individuals using simple random sampling. The results indicate that pending claims were largely caused by factors such as inappropriate emergency conditions (180 cases (62.28%), incomplete documentation (55 cases (19.03%), and other factors (54 cases (18.69%). This situation disrupts hospital cash flow, increases staff workload, and potentially decreases the quality of patient care. Therefore, improved efforts are needed through routine training, the preparation of clear SOPs, increased coordination between units, and the use of information technology so that the claims process runs more optimally and the quality of hospital services is maintained.